Room-Temperature Synthesis of Air-Stable Near-Infrared Emission in FAPbI3 Nanoparticles Embedded in Silica - Lung-Chien Chen (MDPI AG, 2021)
Hybrid organic−inorganic and all-inorganic metal halide perovskite nanoparticles (PNPs) have shown their excellent characteristics for optoelectronic applications. We report an atmospheric process to embed formamidinium CH(NH2)2PbI3 (FAPbI3) PNPs in silica protective layer at room temperature (approximately 26 °C) employing (3-aminopropyl) triethoxysilane (APTES). The resulting perovskite nanocomposite (PNCs) achieved a high photoluminescence (PL) quantum yield of 58.0% and good stability under atmospheric moisture conditions. Moreover, the PNCs showed high PL intensity over 1 month of storage (approximately 26 °C) and more than 380 min of PNCs solutions in DI water. The studied near-infrared (NIR) light-emitting diode (LED) combined a NIR-emitting PNCs coating and a blue InGaN-based chip that exhibited a 788 nm electroluminescence spectrum of NIR-LEDs under 2.6 V. This may be a powerful tool to track of muscle and disabled patients in the detection of a blood vessel.